كـتــابـات الـمـؤرخـيـن الــفـرنـسـيـيـن لـتـاريــخ الـجـزائــر أسـالـيـبها، دوافـعـها، مـمـيزاتها، سـلبـياتـها : The French Historians Writings on the Algerian History: Their Methods, Motives, Advantages, Disadvantages - Ould Beziou, Ahmed; Abdul Hamid, Faisal @ Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
This study aims to elucidate the historical writing methods employed by French historians in documenting the history of Algeria throughout different periods, examining their motivations. It highlights both the positive and negative aspects of these writings. The significance of this research lies in its exploration of a pivotal topic in European and African history, encompassing political, cultural, social, and economic dimensions. It becomes apparent that French historical writings paid considerable attention to their colonies in North Africa, notably emphasizing Algerian history, dedicating both material and intellectual efforts in serving the French administration. Moreover, the study addresses the problematic nature of distortion and misinformation practiced by some French scholars in documenting Algerian history. The researcher utilized a historical methodology to understand the nature and motives behind French writings on Algerian history, employing an analytical and critical approach to scrutinize these writings, aiming to highlight the truth. The study concludes that French historical writing on Algerian history covered ancient and modern history, discussing aspects of land, people, heritage, artifacts, and geography. They established scientific societies, initiated newspapers, and research journals, supported financially by the French administration, reflecting a positive aspect of these historical writings. However, the negative aspects lie in the predominantly shallow, repetitive, and biased studies that often neglect Arab, Ottoman, and even Western sources. Hence, these historical writings require reassessment in line with the requisites of modern historical methodology.